A novel terahertz metasurface based on a single-walled carbon nanotube film for sensing application. Issue 4 (12th January 2022) - Wang, Yue; Zhang, Xiang; Zhang, Xiaoju; Zhou, Tao; Cui, Zijian; Zhang, Kuang
Abstract : A single-walled carbon nanotube film metasurface sensor for detection trace concentrate of pesticide based on the transmission resonance induced by THz surface plasmon polaritons was developed. The proposed sensor has a low detection limit of 10 ng. Abstract : Single-walled carbon nanotubes have attracted extensive research interest because of their fascinating optoelectronic response in the terahertz frequency range. Here, a 1 μm thick isotropic single-walled carbon nanotube film was obtained by vacuum filtration. The absorption and dispersion properties of the film in the range of 0.2–2.0 THz have been studied by terahertz time-domain spectroscopy. The frequency-dependent refractive index, effective dielectric constant, and conductivity of the single-walled carbon nanotube film were extracted from the measured transmission spectra. Based on the above results, we demonstrate a novel terahertz metasurface by etching subwavelength arrays on the surface of the single-walled carbon nanotube film. Experimental and simulated results show that a strongly localized enhanced electromagnetic field can be generated at the device surface under the excitation of incident terahertz waves, which is of great significance for the application of metasurface devices in the field of chemical sensing. We demonstrate the sensor performance of the devices by dropping different concentrations of 2, 4-dichlorophenoxyacetic acid solutions on the device surface at room temperature. The measurement results show that the detection sensitivity of the proposed metasurface sensor is 2.1 × 10 −2 /ppm, and the minimum detection mass is 10 ng. As a complement to traditional terahertz metasurfaces, our work provides a systematic design strategy for guiding the design of carbon nanotube-based metasurfaces, which will open an alternative way for the application of terahertz metasurfaces in the field of biochemical sensing.